تاریخ پر ادارہ تحقیقات اسلامی کی مطبوعات کا تجزیاتی مطالعہ ...................................................................................... Publications of Islamic Research Institute on History: An Analytical Study - فاروق, محمد اجمل (FIKR-O NAZAR فکر ونظر, 2018)
Islamic Research Institute has published books on history with different direction of humanity. These publications explore the variety of research with the causes of rise and fall of nations analysing human qualities and drawbacks. The research material in these publications belong to three sides of history; Islamic Spain, Sciences and Methodology of Hijri Calendar with special reference to four books that take intention of the readers and scholars to provide huge and authentic knowledge to the next generation. This paper explores the need to excite and motivate scholars and researches for enhancing of renaissance of Muslim Ummah with moderation, progressive development and reconstruction of Islamic thought. It enhances the following questions to grant the guidance of Muslim scholarship. What are the methods and techniques to study the history of Muslim tradition in Spain? Is there any connection between Sciences of Muslim age in the past with contemporary time? From Hijri and Christian Calendar, what is the method to be used by scholars during historical research? This article puts the answers of above-mentioned questions with highlighting the works of IRI in the history.